An Anecdotal Case Study in Psychological Anthropology of Two Retired Middle School Teachers’ Perceptions of Classroom Life in the United States - Attwood, Adam I. (Frontiers in Education, 2021)
In this qualitative study, two interviews analyzed in this study suggest how two middle school teachers fostered an inclusive and supportive classroom environment despite the national stress of the Vietnam War during the late 1960s and early 1970s. Half a century later in 2020-2021, similar trends seem to remain just as important in society during national social and political unrest. Implications for social-emotional learning from then and now are discussed. Each of the two participants in this study established centralized control through slightly different means and both used written guidelines and rules while emphasizing prosocial behaviors. Three themes emerged: (1) a syllabus was important in management style, (2) sports, and (3) the national social context—such as the Vietnam War—manifested itself in the discourse of the social environment to affect classroom life. Implications for the socio-spatial context of school architectural layout are explored.